ANALISIS PRODUKTIVITAS CRUSHER PADA PENGOLAHAN BATUBARA UNTUK MENCAPAI TARGET PRODUKSI BULANAN DI PT JAKSA LAKSA UTAMA SITE PT BGG LAHAT SUMATERA SELATAN - Aidil Ilham Pratama; Ahmad Husni; Suhardiman Gumanti (Jurnal Humaniora & Sosial Sains, 2025)
Crushing activities are an important stage in coal processing to meet production targets. This study aims to analyze the productivity performance of the crusher at PT Jaksa Laksa Utama Site PT Budi Gema Gempita during March 2025. The method used includes field observation, recording of daily production data, as well as analysis of effective working time and delay time. The results of the study show a work efficiency of 84.29% with an average effective working time of 15.17 hours/day and an average productivity of 720.9 tons/hour. Factors affecting productivity include delays due to mechanical disturbances, standby due to delays in material supply, and environmental conditions such as high rainfall. Improvement recommendations include optimizing working time, routine maintenance, and increasing coordination between operational units. The implementation of these efforts is expected to support the achievement of coal production targets optimally.